Analisis Kesalahan Newman (Newman Error Analysis-Nea): Perbandingan Ketelitian Antara Siswa Yang Menghafal Dan Tidak Menghafal Alqur’an - mukminah mukminah; riana riana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
Newman (1977) form Australia was defined five specific literacy and numeracy skills as crucial to performance on mathematical word problems: (1) reading error, (2) comprehension error, (3) transformation error, (4) process skills error, and (5) encoding error. The purpose of this study is to comparison Newman Error Analysis (NEA) between students are memorize and not memorize Al-Quran in solving word problem. This research is a qualitative research, and the subject of this research is students in grade 11th of MA in central lombok, with respectively six school in sub-district.. The result of this research is there are differences Newman’s Error Analysis (NEA) Between Students Are Memorize and Not Memorize Al-Quran in Solving Math Word Problems.